The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0101-31222008000100023
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da giberelina e da secagem no condicionamento osmótico sobre a viabilidade e o vigor de sementes de sementes de mamão (Carica papaya L.)

Abstract: Esta pesquisa teve como objetivo avaliar os efeitos da presença ou ausência de giberelina na solução de condicionamento osmótico e da secagem antes e após o condicionamento sobre a qualidade fisiológica de sementes de mamão. As sementes foram condicionadas em soluções de PEG6000 a -0,1 MPa, -1,0 MPa e em água destilada com dois níveis de GA3, 0 ou 200 mg.L-1. Para cada solução osmótica ou água destilada, utilizou-se o delineamento estatístico inteiramente casualizado, com quatro repetições, em esquema fatorial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 14 publications
1
15
0
2
Order By: Relevance
“…Some studies demonstrated a positive effect of plant hormones on germination of this seeds, increasing the germination speed and uniformity of papaya seeds of the "Formosa" group (Tokuhisa et al, 2007a;Lopes et al, 2009). However, studies on seeds of the "Solo" group are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies demonstrated a positive effect of plant hormones on germination of this seeds, increasing the germination speed and uniformity of papaya seeds of the "Formosa" group (Tokuhisa et al, 2007a;Lopes et al, 2009). However, studies on seeds of the "Solo" group are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The use of gibberellins in the germination phase may improve seed vigor and germination in a number of species, as observed here for S. torvum, but they become more important when the seeds are under adverse conditions (Ferreira et al 2005, Lopes & Sousa 2008. However, gibberellins accelerate the germination and emergence of several species, while for others they promote a slight or no response (Soares et al 2009).…”
Section: Research Notementioning
confidence: 59%
“…O efeito prejudicial do GA 3 pode ser comprovado, também, pela percentagem de sementes que não germinaram (22%) e deterioradas (42%). O efeito favorável das giberelinas, na superação da dormência de sementes, é relatado por: Ferronato, (1999), sobre a germinação de sementes de pé-de-anta (Cybistax antisyphilitica) ;Prado Neto et al (2007), sobre sementes de jenipapeiro (Genipa americana); Ferreira et al (2005), sobre sementes de maracujazeiro (Passiflora edulis); Lopes & Souza (2008), sobre a viabilidade e o vigor de sementes de mamão (Carica papaya); e Bernardes et al (2008), sobre sementes de pequizeiro (Caryocar brasiliense). No entanto, as giberelinas nem sempre favorecem a germinação e, em alguns casos, podem ter efeito negativo, como nas sementes de Echinacea angustifolia DC.…”
Section: Resultsunclassified
“…As giberelinas são hormônios vegetais com várias funções no processo germinativo de sementes, no crescimento e no desenvolvimento das plantas (Vieira et al, 2002;Stenzel et al, 2003;Lima-Brito et al, 2006;Tokuhisa et al, 2007;Lopes & Souza, 2008). Podem atuar no crescimento vegetativo do embrião, pelo enfraquecimento da camada de endosperma que envolve e restringe o crescimento desse embrião, e na mobilização de reservas do endosperma (Taiz & Zeiger, 2004).…”
Section: Introductionunclassified